Assessing health facility preparedness in Nepal for addressing climate-related disasters and climate-sensitive diseases - Khanal, Sudeepa; Schubert, Tabea; Boeckmann, Melanie; Pradella, Fabienne (Frontiers in Climate, 2025)
Climate change poses a serious threat to human health and is a key driver of both health system stress and disaster-related health impacts. As climate-related crises become more frequent and intense, the likelihood of climate-induced disasters increases, bringing a wide range of health consequences, including climate-sensitive diseases (CSDs) and exacerbating health inequities. Strengthening disaster preparedness in health facilities is essential for managing increased service demands, ensuring continuity of care, and minimizing the impact of disasters on communities. However, there is limited evidence on how well health facilities are prepared to manage climate-related disasters and deliver CSD diagnosis and treatment services, particularly in low-and middle-income countries (LMICs) such as Nepal. This study aims to address that gap by linking data from the 2021 Nepal health facility Service Provision Assessment survey with local-level climate-related disaster data from the Nepal Disaster Risk Portal (2018–2020). We explore climate related disaster preparedness and the availability of CSD-related services across different types of health facilities, assessing overall emergency preparedness and the availability of six CSD services based on their past exposure to disasters. Furthermore, we compare differences in preparedness and CSD service availability between facilities with high and low levels of disaster exposure. The study provides an overview of how well various types of health facilities are prepared to respond to climate-related disasters and CSDs, while also highlighting disparities in preparedness and service availability across facility types. Although the findings indicate some degree of adaptation of some type of health facilities to climate-related disaster exposure, it calls for comprehensive assessments that integrate all components of a climate-resilient health system as defined by the WHO, to support evidence-based planning and strengthen Nepal’s progress toward a climate-resilient health system.